Ksiądz Zdzisław Grzegorski — ojciec polskiej homiletyki kontekstualnej - Kalbarczyk, Adam (Poznańskie Studia Teologiczne, 2020)
The article reminds and introduces the work of Zdzisław Grzegorski (1930–2012), a theologian from Poznań, a lecturer of homiletics and the editor of the “Biblioteka Kaznodziejska” (Preachers’ Library), called the father of the Polish school of contextual homiletics. The contextual homiletics, which he created and popularized in numerous publications, deals with the relationship of the forms of religious messages to other forms of communication and makes the effectiveness of proclaiming the word of God relevant to communicating. The service of the word creates a peculiar channel of information, consisting of such elements as: theological awareness, disposition of the preacher, the attitude of the recipient, the closer and further context, the language. The communication act on the pulpit has various functions: cognitive, conative, phatic and prophetic. The preacher should check the functioning of the communication channel through the theological and postulative observation. Grzegorski’s concept was developed in a few national symposia and conferences. It had a significant impact on the contemporary Polish homiletic reflection. The communication and contex- tual orientation can be seen in several works of Polish preachers. Nevertheless, Grzegorski’s work demands further development and popularization, so that the contextual understanding and practice of communicating the word of God has been adopted in the Church.